Pengaruh Ukuran Perusahaan dan Solvabilitas terhadap Audit Delay pada Perusahaan Sub Sektor Minyak, Gas dan Batu Bara yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024 - Hanna Febriyani; Taat Kuspriyono (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
The progressive dynamics of the Indonesia Stock Exchange (IDX) encourage accurate and optimized financial statement audits. Every listed company is required to prepare financial statements in accordance with accounting standards and have them verified by independent auditors registered with the capital market authority. Auditing for publicly listed companies demands high responsibility, motivating firms to improve professional standards, including maintaining timeliness in audit reporting. One of the sectors under focus is the oil, gas, and coal subsector, where some companies experience delays in financial reporting, known as audit delay. Factors influencing these delays include firm size and solvency. This study aims to analyze the effect of firm size and solvency on audit delay in companies within the oil, gas, and coal subsector listed on the IDX from 2021 to 2024. The study sample consists of 13 companies meeting the research criteria during this period. Purposive sampling was employed, and data were analyzed using classical assumption tests and multiple linear regression with SPSS version 27. Results indicate that firm size has a significant negative effect on audit delay, while solvency does not have a significant partial effect. Simultaneously, firm size and solvency significantly influence audit delay, suggesting that both variables collectively affect the timeliness of financial statement submission.